2020
DOI: 10.3389/fonc.2020.01233
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Sonic Hedgehog Signaling Suppresses Glioma Stem-Like Cells Likely Through Inducing Autophagic Cell Death

Abstract: Glioblastoma (GBM) often recurs after radio-and chemotherapies leading to poor prognosis. Glioma stem-like cells (GSCs) contribute to drug resistance and recurrence. Thus, understanding cellular mechanism underlying the growth of GSCs is critical for the treatment of GBM. Here GSCs were isolated from human U87 GBM cells with magnetic-activated cell sorting (MACS) using CD133 as a marker. The CD133 + cells highly expressed sonic hedgehog (Shh) and were capable of forming tumor spheroids in vitro and tumor in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 58 publications
0
23
0
Order By: Relevance
“…GBM is still not cured well, indicating the necessity of alternative therapies (Bhuvanalakshmi et al, 2018;Chen, Luo, Wen, & Pi, 2020;Guo et al, 2020;H. C. Hung, Liu, Chuang, Su, & Gean, 2020;T.…”
Section: Gliomamentioning
confidence: 99%
“…GBM is still not cured well, indicating the necessity of alternative therapies (Bhuvanalakshmi et al, 2018;Chen, Luo, Wen, & Pi, 2020;Guo et al, 2020;H. C. Hung, Liu, Chuang, Su, & Gean, 2020;T.…”
Section: Gliomamentioning
confidence: 99%
“…Although autophagy inhibition has been shown to be a promising strategy for cancer treatment ( Yang et al, 2015 ; Pan et al, 2016 ; Buccarelli et al, 2018 ; Bie et al, 2021 ), there are some studies indicating that autophagy activation can also be utilized in cancer treatment. For example, autophagy activation, not inhibition, increases the sensitivity of GSCs to drugs ( Hung et al, 2020 ). Another study showed that the co-suppression of mTORC1, histone deacetylase, and estrogen receptor 1 decreases the number of CSCs via autophagy activation in TNBC ( Sulaiman et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Shh signaling pathway mediates cell proliferation, stem cell fate determination, and differentiation of both normal neural stem cells (NSCs) and GSCs [ 104 , 105 ]. LDE225, a smoothened antagonist that blocks the hedgehog pathway, induces autophagic cell death in GSCs, and CD133-positive cells are more sensitive to LDE225-derived cell death than CD133-negative cells [ 79 ]. Moreover, a separate study showed that LDE225 inhibited the expression and nuclear translocation of Gli proteins, which are transcriptional effectors of the Shh signaling pathway [ 106 ].…”
Section: Strategies Targeting Gscsmentioning
confidence: 99%